Conceptualizing Job Satisfaction and Its Determinants: A Systematic Literature Review - Wyrwa, Joanna; Kaźmierczyk, Jerzy (Journal of Economic Sociology, 2020)
Job satisfaction is considered an important aspect of employee behavior. This article focuses on a critical analysis of the accompanying literature to determine the various factors that shape job satisfaction and to gauge their relative signifi-cance in conditioning employee behavior. The conceptualizations of job satisfac-tion in the existing literature are multitudinous, reflecting the breadth of critical perspectives on the subject. A systematic literature review, therefore, consisted of: (a) isolating databases and a set of publications; (b) selecting publications and developing a database; and (c) conducting bibliometric analysis, content analy-sis, and testing the relevance of results to further research. The review included publications from the years 2000–2018 and covered psychology, sociology, eco-nomics, and management science. Analysis of previous theoretical publications and empirical studies reveals that they are not without their cognitive and meth-odological limitations. Even at the level of definition, despite numerous criti-cal attempts to clarify exactly what constitutes job satisfaction, an unambiguous and clear-cut conception has yet to surface. Equally, critical consensus is lack-ing among researchers over what contributes to job satisfaction, and divergent research approaches have been adopted as a result. Indeed, despite the rising popularity of job satisfaction studies, some of these factors have yet to be ex-plored fully, while some research has yielded contradictory results regarding the strength of the influence of certain factors on job satisfaction. This paper fills this gap and, through a systematic analysis of the literature, indicates the direction in which current research is headed.